2003
DOI: 10.1021/jf0300691
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of Citrus Limonoids in Humans

Abstract: This study utilizes liquid chromatography/mass spectrometry (LC-MS) to analyze the plasma of four groups of four healthy male and female subjects administered high doses of pure limonin glucoside (0.25-2.0 g in 200 mL of buffered water) for the presence of limonin to establish the absorption, metabolism, and bioavailability of citrus limonoids to humans. The plasma analysis revealed increasing amounts of limonin associated with increasing doses of limonin glucoside among the subject groups in mean maximum conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
57
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 27 publications
2
57
2
Order By: Relevance
“…All naturally occurring citrus limonoids contain a furan ring attached to the D-ring, at C-17, as well as oxygen containing functional groups at C-3, C-4, C-7, C-16, and C-17 [146]. Citrus fruits and their closely related genera contain about 36 limonoidaglycones and 17 limonoidglucosides [147]. Citrus limonoids and their glucosides, the watersoluble triterpenoid compounds that occur naturally in citrus fruit and citrus juice in amounts comparable to vi-tamin C, can be reclaimed from citrus processing and citrus seeds as by-products in large quantities [146].…”
Section: Limonoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…All naturally occurring citrus limonoids contain a furan ring attached to the D-ring, at C-17, as well as oxygen containing functional groups at C-3, C-4, C-7, C-16, and C-17 [146]. Citrus fruits and their closely related genera contain about 36 limonoidaglycones and 17 limonoidglucosides [147]. Citrus limonoids and their glucosides, the watersoluble triterpenoid compounds that occur naturally in citrus fruit and citrus juice in amounts comparable to vi-tamin C, can be reclaimed from citrus processing and citrus seeds as by-products in large quantities [146].…”
Section: Limonoidsmentioning
confidence: 99%
“…The citrus limonoidsobacunone, limonin, nomilin and their glucosides, and some aglycones inhibit chemically induced carcinogenesis and a series of human cancer cell lines, with remarkable cytotoxicity against lung, colon, oral and skin cancer in animal test system and human breast cancer cells [151]- [153]. Pure limoninglucoside and limonin, (its water insoluble relative lacking glucose) have been found to possess significant antitumor properties in animal tests and with human cells [147].…”
Section: Limonoidsmentioning
confidence: 99%
“…whether they are absorbed intact or as metabolites. On the other hand, it is well known that lifestyle, behavior, diets, and basal metabolism of the subjects are more important affecting factors than age, gender, body weight, and plasma volume (Manners et al, 2003) in bioavailability determination. Therefore, standardized experimental conditions controlling such critical factors of absorption in vivo and in vitro is a must despite individual human variability.…”
Section: Absorption Of Phytochemicalsmentioning
confidence: 99%
“…Generally, it is water soluble; yet few aglycone forms of liminoids are insoluble. According to Manners et al (2003) liminoid metabolites are found in human after ingestion of citrus juice containing limonin glucoside which may undergo epimerization from limonin glucoside to epilimonin (m/z 471.2). This may be from reaction pathways of hydrolization of glucoside moiety followed by lactonization.…”
Section: Phytochemical Absorptionmentioning
confidence: 99%
“…Limonin and nomilin also inhibited in vitro HIV-1 protease activity. The relevance of all of these potential health benefits is increased by a recent discovery that limonin 17-P-D-glucopyranoside was absorbed from the gastrointestinal tract of human volunteers (41). Following consumption of a 200 ml drink containing 0.25-2.0 g of limonoid glucoside, blood was collected and analyzed for the presence of limonoids.…”
mentioning
confidence: 99%